Cell investigation into the biocompatibility of adult human dermal fibroblasts with PCL nanofibers/TiO2 nanotubes on the surface of Ti–30Ta alloy for biomedical applications. Issue 8 (4th June 2020) - Capellato, Patrícia; Silva, Gilbert; Popat, Ketul; Simon‐Walker, Rachael; Alves Claro, Ana Paula; Zavaglia, Cecilia
Abstract: The polymer poly(ε‐caprolactone) (PCL) has been used in the biomaterial field for its relatively inexpensive price and suitability for modification. Also, its chemical and biological properties are desirable for biomedical applications. The electrospinning process has been used for producing polymer fibers of PCL due in large part to an increased interest in nanoscale properties and technologies. Moreover, the use of biocompatible polymers for the viability of cell growth is a promising alternative to improve osseointegration. Characterization techniques such as scanning electron microscopy and contact angle were used for analyses of samples. Adult human dermal fibroblasts (neonatal) were utilized to evaluate the biocompatibility of the association of the electrospinning process of the biocompatible polymer (PCL) with TiO2 nanotubes on the Ti–30Ta alloy surface. The results of this study showed a favorable response for adhesion on the surface. This promising material is due to the modulation of the biological response.